Mini-Nutritional Assessment Questionnaire for Assessing the Nutritional Status of Patients with Chronic Obstructive Pulmonary Disease: A Cross-sectionalStudy - Bam, Niraj; Shrestha, Bibek; Timla, Bipashna; Pokhrel, Kailash Mani (Journal of Institute of Medicine Nepal, 2025)
Introduction Chronic obstructive pulmonary disease (COPD) has systemic effects like malnutrition that increase morbidity and mortality. Nutritional assessment in COPD is not adequately addressed in Nepal even though the assessment is clinically relevant. The objective of the study is to determine the nutritional status of COPD patients based on MNA and to evaluate the correlation between the MNA and demographic, anthropometric and spirometry variables. Methods The study involved 140 stable COPD patients, who were studied using cross-sectional study design. Mini Nutritional Assessment (MNA) was used to determine the nutritional status. Demographic variables, anthropometric and spirometry parameters and clinical variables were taken. The associations were compared based on chi-square, one-way ANOVA, and Pearson correlation whereby p < 0.05 was regarded as significant. Results GOLD stage was associated with nutritional status (p = 0.034), and BMI differed across nutritional categories (p < 0.001). No association was observed between nutritional status and spirometry indices or dyspnea grade (all p > 0.05). MNA score showed a moderately positive correlation with BMI (r = 0.501, p < 0.001), whereas no correlation was noted with FEV1 or mMRC grade. These findings suggest that nutritional impairment is more closely related to anthropometric parameters than to pulmonary function. Conclusion COPD patients have a high prevalence of malnutrition, and poorer nutritional status was associated with more advanced GOLD stages. COPD management should include routine MNA screening and early nutritional interventions to improve clinical outcomes.